Achieving high power-conversion efficiency of MASnI3/CuGaSe2 lead-free perovskite solar cells - Mekhaznia, Nourelhouda; Zaidi, Beddiaf; Alali, Ahmet Sait; Barkhordari, Ali (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
Lead-free perovskite combined with chalcogenide thin films such as CIGS compounds present viable alternatives for sustainable photovoltaic fabrication. This study investigates and optimizes a dual-absorber solar cell based on the FTO/TiO2/MASnI3/CGS/Ag structure using SCAPS-1D simulations. The perovskite band gap was tuned by adjusting the halide composition to determine the optimal value for maximizing power conversion efficiency, followed by systematic optimization of absorber thickness, acceptor density, defect density, series/shunt resistances, and operating temperature. The optimized device achieved an efficiency of 32.26%, open-circuit voltage (VOC) of 1.13 V, short-circuit current density (JSC) of 34.90 mA/cm2 and fill factor (FF) of 81.55%. These findings validate the potential of integrating lead-free perovskites with CGS to advance sustainable photovoltaic technologies.
Keywords: Lead-free perovskite; MASnI3; Band gap tuning; CuGaSe2; ABSORBER LAYER; PERFORMANCE; TEMPERATURE; THICKNESS; TRANSPORT; DENSITY; Chemistry; Physics